Infrastructure Governance in Times of Crises: A Research Agenda for Australian Cities. Issue 1 (2nd January 2022) - Alizadeh, Tooran; Clements, Rebecca; Legacy, Crystal; Searle, Glen; Kamruzzaman, Md.
ABSTRACT: Planning should deliver urban infrastructures that nurture places and people. However, the misalignment between strategic plans and delivered projects reveals critical governance gaps, with little clarity surrounding for whom and what ends infrastructures serve. This positioning piece proposes an infrastructure governance research agenda focused on the integration of planning, funding, and social legitimacy of projects, and the reality of multiple ongoing crises. Most importantly, the proposed research agenda calls for a First Nation voice at the heart of infrastructure decision-making as part of the planning profession's contribution to the Treaty process that Australia desperately needs to move forward.